Proceedings of the Internet Measurement Conference 2018 2018
DOI: 10.1145/3278532.3278561
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Cross Border Web Tracking

Abstract: A tracking ow is a ow between an end user and a Web tracking service. We develop an extensive measurement methodology for quantifying at scale the amount of tracking ows that cross data protection borders, be it national or international, such as the EU28 border within which the General Data Protection Regulation (GDPR) applies. Our methodology uses a browser extension to fully render advertising and tracking code, various lists and heuristics to extract well known trackers, passive DNS replication to get all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
(36 reference statements)
0
34
0
Order By: Relevance
“…Therefore, it is important to design practical, web transparency tools such as CONRAD, which will be readily available to privacy researchers, regulators and end-users. These tools can be used by plain users or the research community to investigate personal data leakage and anonymity on the web, due to 3rd parties' activities such as CSync [21].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, it is important to design practical, web transparency tools such as CONRAD, which will be readily available to privacy researchers, regulators and end-users. These tools can be used by plain users or the research community to investigate personal data leakage and anonymity on the web, due to 3rd parties' activities such as CSync [21].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We then use the filter lists to classify follow-up thirdparty requests that would have been blocked by the lists. This technique has been extensively used in the previous works [23,[28][29][30] (for more details, see Table 12 in the Appendix). We classify a request as blocked if it matches one of the conditions: -the request directly matches the list.…”
Section: Measuring Tracking Requestsmentioning
confidence: 99%
“…GDPR is newly introduced, and so there have only been a handful of measurements and analyses: [6] concluded that tracking flows mostly stay within the EU. In a periodic survey of top 500 sites, [3] found that around one-sixth of websites (15.7%) had reorganised privacy policies by May 25, 2018.…”
Section: Related Workmentioning
confidence: 99%